SARAWATA CHURNA TREATMENT AMELIORATES THE COGNITION IMPAIRMENTS IN LITHIUM-PILOCARPINE INDUCED EPILEPTIC RATS - Pugazhandhi Bakthavatchalam, Arul Amuthan, Rajesh Thangarajan, Venu Madhav Nelluri, R Huban Thomas, Sudarshan Surendran* (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
The purpose of this study was to see how Saraswata Churna (SC) affected the cognition of 4 month old adult male Wistar rats who had epilepsy. One of the most common epilepsy symptoms is memory impairment. The elevated plus maze (EVPM) and Morris water maze (MWM) tests were used to assess the effect of SC on rat learning and memory. Pilocarpine (270 mg/kg BW, i.p.) was used to induce epilepsy.Saraswata Churna's effect on pilocarpine-induced epilepsy was evaluated. Saraswata Churna (300 mg/kg b.w. orally) improved the rats' cognitive performance, as shown by reduced latency in the EVPM, decreased escape latency during training, and more time spent in the target zone during recovery in the MWM. Saraswata Churna (300 mg/kg b.w. oral) has memory-enhancing action comparable to phenytoin (30 mg/kg b.w. i.p.). Saraswata Churna demonstrated memory-improving efficacy in rats, most likely because to its phytoconstituents, which have anti-inflammatory, antioxidant, and anticonvulsive properties. Keywords: Saraswata Churna, Epilepsy, Dementia, Cognition, Neurocognitive illness, acetylcholine esterase inhibition,